2019
DOI: 10.4103/jfcm.jfcm_58_18
|View full text |Cite
|
Sign up to set email alerts
|

A profile of physical activity, sedentary behaviors, sleep, and dietary habits of Saudi college female students

Abstract: BACKGROUND:Few studies have reported valid comprehensive data on lifestyle habits of Saudi college females. In addition, studies on sedentary behaviors (SBs) and the duration of sleep of Saudi college students are rare. Saudi females appear to be less physically active and therefore, at a higher risk of noncommunicable diseases (NCDs). Therefore, the purpose of this study was to investigate lifestyle patterns of Saudi college females, including physical activity (PA), SBs, duration of sleep, and dietary habits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 36 publications
(57 reference statements)
1
10
4
Order By: Relevance
“…Other studies conducted among medical students have also reported unhealthy dietary habits reiterating the stress eating narrative which is likely to affect medical and dental students. A study reported by Alzamil et al [ 23 ] stated that consump-tion of sugary foods among medical students was about 60% which was found to be high in the present study as well. Another study closer to home reported that only 10% of medical students consumed fruits and vegetables on a daily basis, proving unhealthy dietary habits [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…Other studies conducted among medical students have also reported unhealthy dietary habits reiterating the stress eating narrative which is likely to affect medical and dental students. A study reported by Alzamil et al [ 23 ] stated that consump-tion of sugary foods among medical students was about 60% which was found to be high in the present study as well. Another study closer to home reported that only 10% of medical students consumed fruits and vegetables on a daily basis, proving unhealthy dietary habits [ 24 ].…”
Section: Discussionsupporting
confidence: 79%
“…The unhealthy dietary habits are more prevalent in Saudi adult population specifically in females than males [ 28 , 29 ]. Our present study agrees with these findings showing overall less interest towards their healthy diet (71.4%), while females exhibited significant less attention towards their healthy diet during the pandemic as compared to before (69.5 vs. 71.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this review will provide evidence for considering PA intervention incorporating smartphone application and considering the inclusion of BCT components in smartphone applications for promoting PA among university students. If our meta-analyses will result in positive effects, this review will support the inclusion of smartphone application in PA intervention as a novel strategy to reduce the problems of physical inactivity among university students which have not change in recent years [43,44,45,46].…”
Section: Discussionmentioning
confidence: 90%